STRUKTUR MODAL USAHA KECIL SENTRA KULIT DI SUKAREGANG, GARUT - Budiana Gomulia; Vera Intanie Dewi (Center for Economic Studies Universitas Katolik Parahyangan, 2011)
Sukaregang Leather craftsmen Centre in Garut is known nationally, and is also a pride of Garutan people, but unfortunately its growth has not shown any outstanding outcomes. The problem of capital-is mentioned as one of the issues. Meanwhile, as we know that the Ministry of Economic, Small and Medium Enterprises (KEMENKOP) aims at building healthy and strong small, micro and medium enterprises because of its capability to collect its own capital or equity capital and to increase the benefits of credit utilizing as a couple of the reasons. Population of this research is small-scale craftsmen in Sukaregang Leather Craftsmen Centre in Garut taken by purposive sampling. Data collection methodology is focus group discussions and surveys. Purpose of this research is to explain capital structure in general. From the research on micro- and small-scale entrepreneurs in Sukaregang Leather Craftsmen Centre in Garut, we know that: capital structure is not optimum yet, 1). Equity capital accumulation is very limited; 2). Proportion of a loan utilized for business operational, continuity and expansion is too little; and 3) There are potencies of ineffective loan utilizing. Researchers find some worrying facts: a). Both suppliers and customers are 'still reluctant' to give capital aid; b). Koperasi, BPR, and public banks are known to be able to giant a loan for craftsmen, but high interest rate and other costs, required collateral are factors which inhibit them to get a credit; c). Due to some middle-scale entrepreneurs who do not pay their credit appropriately, these entrepreneurs in this center are